Influência do disclosure voluntário sobre o custo de capital de terceiros dos clubes de futebol do Brasil - Carneiro Junior, Erivaldo da Silva (2015)
This study aimed to investigate the relationship between the level of voluntary disclosure and the cost of debt of soccer clubs in Brazil. As theoretical basis, we used the Theory of Disclosure studied by Verrechia (2001), in the case of the present study Efficiency-based research, as well as being shown the calculations of capital costs, such as presentation of national and international research the subject. Regarding the methodology, the sample was formed by convenience, totaling 20 clubs studied during 2008-2012, to the level of disclosure and the control variables, and from 2009 to 2013, for the cost of debt. The analysis of disclosure and the calculations of the cost of debt, liquidity, obtaining gross revenue and auditing information were obtained from the DFP (Financial Statements) and when possible extrapolated to other statements published by the clubs. Was made an adaptation to the metric of voluntary disclosure of Murcia (2009), which originally had 93 items and in the end, for adaptation to the reality of sport were 73, divided into three groups: economic (33), social (14) and environmental (34). Analysis was made of the disclosure by the club, which gave the overall ranking and group. Calculating the cost of capital was carried out by club and then was made a general ranking of clubs with this variable. The statistical tool used was the panel data analysis, which according tests indicated the regression in fixed effects in cross-section, with an explanatory power of the variables of 16.62%. The research hypothesis can not be proven because of the statistical insignificance of the variables, while indicating that there is an inverse relationship to the cost of capital. As study limitation, the lack of standardization was checked in DFP by the clubs, often making it difficult to obtain the data for analysis and panel data technique is indicated for longer time series and is indicated to be made new studies with larger series.